Isolation and Microbiological and Molecular Identification of Brucella abortus in Cattle and Pigs, Slaughtered in Cattle Sheds Located in Northern Sierra of Ecuador - Maritza Celi-Erazo; Elizabeth Minda-Aluisa; Lisbeth Olmedo-Pinchao; Lenin Ron-Garrido; Tania Ortega-Sierra; Julián López-Balladares; Marlon Carlosama-Yépez; Santiago Gonzalón-Alcarraz; Jacobus H. de Waard; Claude Saegerman; Jorge Ron-Román; Washington Benítez-Ortiz (MDPI AG, 2025)
Brucellosis remains an underreported zoonotic disease in Ecuador. Its control program in cattle integrates diagnostic testing, vaccination, and eradication incentives, although participation is largely voluntary. Since 2025, vaccination has become compulsory nationwide. Human surveillance remains largely passive, and strain-level data are very limited. This study applied an integrated approach, combining serology (Rose Bengal and SAT-EDTA), microbiological culture, and molecular diagnostics, to assess the presence and diversity of Brucella spp. in cattle and pigs from six slaughterhouses in the northern Andean highlands. A total of 2054 cattle and 1050 pigs from Carchi, Imbabura, and Pichincha were sampled. Among cattle, 133 (6.5%; 95% CI: 5.5–7.6) were seropositive, and viable B. abortus strains were isolated from 17 (12.8%). Genus identification was confirmed by IS711-PCR, while species- and biovar-level differentiation was achieved with AMOS-PCR; additional assays targeting the ery gene and RB51 marker were used to distinguish field from vaccine strains. Biotyping and molecular analysis revealed a predominance of B. abortus biovar 4 (13/17 isolates) over biovar 1, all confirmed as field strains. In pigs, 10 animals (0.95%) tested seropositive, but no isolates were recovered, highlighting limitations of serology in swine. Most livestock, including the positives, originated locally, reinforcing the representativeness of our findings. The successful isolation and molecular characterization of B. abortus demonstrates the value of combining diagnostic strategies beyond serology. These results underscore the utility of active surveillance when supported by traceability systems; this approach may also contribute to guide interventions to reduce infection risk in livestock and humans.